2009
DOI: 10.1016/j.chemosphere.2008.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of iron ochre from mine drainage treatment for removal of phosphorus from wastewater

Abstract: Treatment of polluting discharges from abandoned coal mines in the UK currently produces ca 30,000 t y(-1) of hydrous iron oxides ("ochre"), for which there is no major end-use, but which has previously been shown to have potential for removing P from wastewater and agricultural runoff. The efficiency of ochre for P removal from wastewater was investigated in experiments at two sites in the UK: Leitholm in Scotland and Windlestone in England. The three-year experiment at Leitholm involved diverting secondary-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 16 publications
(10 reference statements)
2
48
0
Order By: Relevance
“…Dobbie et al (2009) observed similar effects in their iron ochre-based P filters. P removal rates by concentration were inversely related to flow and declined during the different phases of the experiments, probably due to clogging.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Dobbie et al (2009) observed similar effects in their iron ochre-based P filters. P removal rates by concentration were inversely related to flow and declined during the different phases of the experiments, probably due to clogging.…”
Section: Discussionsupporting
confidence: 61%
“…Different reactive mateManuscript received September 2011 rials have been tested and studied to intensify nutrient removal, e.g. side-products containing iron or other metals (Dobbie et al 2009, Penn and Bryant 2006, Shilton et al 2006, and natural deposits (Arias et al 2001, Gill et al 2011, Renman 2008, Søvik and Kløve 2005. The idea of removing nutrients from agricultural runoff water using filters has recently arisen in many countries (Penn and Bryant 2006, Ballantine & Tanner 2010, Falk Øgaard 2010, Kjaergaard, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale wastewater treatment Dobbie et al (2009) investigated P retention by ochre (hydrous iron oxide) filters at the Leitholm (south-east Scotland) and Windlestone (north-east England) wastewater treatment plants (the experiments were also described in Heal et al 2004). At Leitholm, with settling as the primary treatment and biological filter as the secondary treatment, they studied a tertiary treatment step with granular ochre or ochre pellets (volume 2.1 m 3 ).…”
Section: P Removal In Wastewater Filter Bedsmentioning
confidence: 99%
“…Iron-rich sludge from treatment of acidic mine wastewater (MWS), which has similar or higher iron content compared to iron-rich WWS, has also been tested for its sorption capacity for phosphate from biologically treated wastewater (Dobbie et al 2009;Heal et al 2003Heal et al , 2005Sibrell et al 2009;Wei et al 2008) with maximum sorption capacity of 30 mg-P/g-MWS-dw (Heal et al 2003;Wei et al 2008). This is comparable to the values reported by Ippolito et al (2011) in a recent review on WWS uses, and 30 to[200-fold better than other minerals and waste products like slags and ashes of different origin (Heal et al 2003).…”
Section: Introductionmentioning
confidence: 99%